Psychological impacts of COVID-19 on Vietnamese health workers over the prolonged restricted COVID-19 responses: a cross-sectional study - Tran, Bach (2023)
Objective We assessed the psychological impact posed by COVID-19 and its associated factors on the healthcare workforce nationwide during the peak of Vietnam’s fourth outbreak. Design A cross-sectional study. Setting Our study was conducted in 61 provinces of Vietnam. Methods A total of 2814 healthcare professionals in 61/63 provinces of Vietnam. An online questionnaire using Patient Health Questionnaire-9 (PHQ-9), Perceived Stress Scale-4 (PSS-4) and Generalised Anxiety Disorder-7 (GAD7) scales was distributed randomly to a subgroup of 503 respondents. Primary and secondary outcome measures To determine the impact of COVID-19 on the psychological of health workers, we conducted analyses to test a primary hypothesis related to participants based on three main scales including PHQ-9, PSS-4 and GAD-7 scales. Results Nearly half (49.7%) of healthcare workers experienced mild depression symptoms, 34.0% underwent moderate anxiety symptoms and 49.3% reported highstress levels. Respondents who had a monthly income below 5million VND (~US$212) and had more than 3 days of duty per week had a higher score on the anxiety scales. Compared with medical doctors, nurses/midwives had lower PHQ-9 (Coef=−2.53; 95% CI=−3.71 to −1.36) and GAD-7 scores (Coef=−2.36; 95% CI=−3.56 L to −1.16). Increased workload and work time was the harmful factor that increase the PHQ-9, GAD-7 or PSS-4 scores. More than half (53.9%) of respondents stated no demand for mental healthcare services. Conclusions Health workers who gained less financial rewards are reported to have higher levels of mental distress than others, implying the need for a raise in basic salary as well as compensation and encouragement schemes. To tackle hesitancy in seeking mental help, integrating online mental health therapy with e-health consultations via social media can be strategically implemented to augment service delivery, and simultaneously enhance the standard of mental health services.